Effect of verbal coaching instruction on scanning activity in elite U19 female football players - Mirjam Hintermann; Jörg Fuchslocher (Bern Open Publishing, 2023)
Introduction To perform a successful action in football, players must constantly recognize the given affordances and their surroundings on the field before and during action (McGuckian et al., 2020). Therefore, having the ability to temporarily detach the view from the ball and move the head to scan the environment to identify and recognize information, could affect the quality of the subsequent action (Jordet et al., 2020). This ability might depend on players technical skills, which give a player more opportunities to exploit given affordances (Aksum et al., 2021). Explicit verbal coaching instructions are used to develop these skills in trainings and games. However, there is little evidence that support this coaching strategy. The aim of this study was to investigate how scanning activity without, and with instruction affect player's performance in 4v4 elite U19 female football players. Hypotheses were: i) scan frequency is higher in more skilled players, ii) instruction leads to higher scan frequency, and iii) higher scan frequency increases the quality of the subsequent action. Methods Twenty-five (17.57 ±0.69 years) female players were recruited from two elite football clubs. All players participated twice in a 4v4 small-sided game (SSG). The first SSG was conducted with no special rules. At the beginning and during mini-breaks of the second SSG, players were instructed to constantly look away from the ball and scan the environment before the first ball touch (Jordet et al., 2020). SSG's were video captured and will be analyzed by three experts. Frequency and time of scans before and during action as well as quality and speed of subsequent technical-tactical action will be assessed. Dependent variables will be analyzed using two factorial (instruction x group) analyses of variance (i, ii) and mixed models (iii). Results As the present study was conducted recently, the results will be presented at the conference. However, a previous pilot study showed significantly higher scan frequency after instruction in higher skilled U17 female football players (p < 0.001). It also appeared that higher skilled players are more likely to take advantage of instruction in terms of speed and quality of the subsequent actions. Discussion This study could provide important initial insights into the scanning activity of U19 female football players. Further, implications for coaching instruction on scanning activity and how this affects the quality of subsequent actions, may impact future coaching strategies. References Aksum, K. M., Pokolm, M., Thue Bjørndal, C., Rein, R., Memmert, D., & Jordet, G. (2021). Scanning activity in elite youth football players. Journal of Sports Sciences, 39(21), 2401-2410. https://doi.org/10.1080/02640414.2021.1935115 Jordet, G., Aksum, K. M., Pedersen, D. N., Walvekar, A., McCall, A., & Priestley, D. (2020). Scanning, contextual factors, and association with performance in English premier league footballers: An investigation across a season. Frontiers in Psychology, 11, Article 553813. https://doi.org/10.3389/fpsyg.2020.553813 McGuckian, T. B., Cole, M. H., Chalkley, D., Jordet, G., & Pepping, G.-J. (2020). Constraints on visual exploration of youth football players during 11v11 match-play: The influence of playing role, pitch position and phase of play. Journal of Sports Sciences, 38(6), 658-668. https://doi.org/10.1080/02640414.2020.1723375